The teahouse under socialism the decline and renewal of public life in Chengdu, 1950-2000 - Wang, Di 1956- (Ithaca, New York Cornell University Press, 2018)
To understand a city fully, writes Di Wang, we must observe its most basic units of social life. In The Teahouse under Socialism, Wang does just that, arguing that the teahouses of Chengdu, the capital of Sichuan Province, are some of the most important public spaces―perfect sites for examining the social and economic activities of everyday Chinese.

Wang looks at the transformation of these teahouses from private businesses to collective ownership and how state policy and the proprietors’ response to it changed the overall economic and social structure of the city. He uses this transformation to illuminate broader trends in China’s urban public life from 1950 through the end of the Cultural Revolution and into the post-Mao reform era. In doing so, The Teahouse under Socialism charts the fluctuations in fortune of this ancient cultural institution and analyzes how it survived, and even thrived, under bleak conditions.

Throughout, Wang asks such questions as: Why and how did state power intervene in the operation of small businesses? How was "socialist entertainment" established in a local society? How did the well-known waves of political contestation and struggle in China change Chengdu’s teahouses and public life? In the end, Wang argues, the answers to such questions enhance our understanding of public life and political culture in the Communist state.--Provided by publisher.
Introduction : urban political transitions under socialism -- The demise of the Chengdu teahouse guild and the fall of small business -- State control and the rise of socialist entertainment -- The decline of public life under Mao's rule -- The resurgence of teahouses in the reform era -- Urban residents and migrant workers in public life -- The power of mahjong -- Conclusion : the state, the teahouse, and the public sphere.
Includes bibliographical references and index.
Keywords: Tearooms -- History -- 20th century. -- China -- Chengdu; Socialism and culture -- History -- 20th century. -- China -- Chengdu; Chengdu (China) -- Social life and customs -- 20th century; Chengdu (China) -- Politics and government -- 20th century